Clinical significance of FOXN3 expression in Indian breast cancer patients - Sheersh Massey; Mohammad Aasif Khan; Safia Obaidur Rab; Syeda Maryam Husain; Asifa Khan; Sadaf; Zoya Mallik; Saad Mustafa; Rahul Kumar; Maria Habib; S. V. S. Deo; Syed Akhtar Husain (Scientific Reports)
Abstract Globally, breast cancer is the most common cancer to affect women. There are different molecular and pathological factors that are involved in the uncontrolled proliferation of breast cancer cells. FOXN3 that is member of Forkhead box family proteins is well recognized for having a crucial role in different biological processes and is reported to be dysregulated in various malignancies. The studies to evaluate the significance of the FOXN3 gene in progression of breast cancer are still under progress. We in the current study aim to examine the FOXN3 gene expression in Indian breast cancer patients and find its clinical relevance. FOXN3 expression analysis using RT-PCR, immunohistochemistry, and western blotting was performed in tumor and normal tissue collected from 142 sporadic breast cancer patients. To identify the genetic aberrations in FOXN3 gene automated DNA sequencing was done. FOXN3 expression study revealed the elevated expression of FOXN3 mRNA in 61.26% of the cases whereas FOXN3 protein was seen to be overexpressed in 59.15% cases. Further, it was found that the elevated expression of FOXN3 mRNA was significantly correlated with the post-menopausal (p = 0.003) status and positive lymph node status (p = 0.049) of the patients. The FOXN3 protein expression also exhibited the significant association with menopausal status (p = 0.008), lymph node status (p = 0.001) and clinical stage (p = 0.018) of the patients. However, we did not find any mutation in the DNA binding domain of the FOXN3 gene in the Indian breast cancer cases. Our findings indicates that overexpression of FOXN3 gene in Indian breast cancer cases can have a potential role in breast cancer progression especially in advanced clinical stages.